Arsenic entrapment in reactive columns of residual soils - Carro Pérez, Magalí Evelín (2013)
The purpose of this research is to evaluate the aptitude of two residual soils for the remediation of groundwater contaminated by arsenic (As). Batch and soil column tests were performed to evaluate removal of As from water. Permeable soil columns were prepared with mixtures of sand (90%) and two lateritic soils (10%). Results showed that removal of As in batch tests ranged from 95-99% when using a solid-liquid ratio equal to 1:10. Experimental results obtained in the soil column tests and calibrated simulation models showed that the amount of water that can be decontaminated depends on the initial As concentration and the flow rate. Maximum adsorption capacities in bath test and removal efficiency in soil columns tests clearly relates with the amount of iron compounds in the solid phase. The quality of residual soil samples are related to a high iron content to favor As removal and low clay-size particle content to achieve acceptable flow rates for water purification in low-cost permeable filters and permeable reactive barriers.